THE CHARACTERISTIC FEATURES OF HISTORICAL AND DEMOGRAPHIC PROCESSES IN SIRDARYA REGION IN THE SOVIET PERIOD (Scientific journal of the Fergana State University, 2023)
The study of the historical-demographic processes in all regions of Uzbekistan is one of the most important problems. The assessment of the demographic situation in Sirdarya region, which influenced on growing and reduction of the population, relying on numerical data